PENGARUH HARGA TERHADAP NIAT BERPERILAKU DAN KUALITAS LAYANAN PADA MASKAPAI PENERBANGAN FIREFLY DIBANDA ACEH - Maudi Mauliza, Ahmad Nizam (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This study aims to determine the effect of price on behavioral intention and service quality. The sample used in this research is 200 respondents who are consumers of Firefly Airline in Banda Aceh. Purposive Sampling is used as a sampling technique. Simple regression analysis method is used as an analytical method to determine the effect of the variables involved. The results of this study indicate that prices have a significant effect on behaviour intention and service quality. So the higher the price applied by the company, the higher the influence on the behaviour intention of passengers and the higher the price applied by the company the higher the influence on the service quality that perceived by the passengers            Keyword : Price , Behavioral  Intention, Service Quality, Firefly Airlines